Conserved brain myelination networks are altered in Alzheimer's and other neurodegenerative diseases. Issue 3 (26th October 2017) - Allen, Mariet; Wang, Xue; Burgess, Jeremy D.; Watzlawik, Jens; Serie, Daniel J.; Younkin, Curtis S.; Nguyen, Thuy; Malphrus, Kimberly G.; Lincoln, Sarah; Carrasquillo, Minerva M.; Ho, Charlotte; Chakrabarty, Paramita; et al.
Abstract: Introduction: Comparative transcriptome analyses in Alzheimer's disease (AD) and other neurodegenerative proteinopathies can uncover both shared and distinct disease pathways. Methods: We analyzed 940 brain transcriptomes including patients with AD, progressive supranuclear palsy (PSP; a primary tauopathy), and control subjects. Results: We identified transcriptional coexpression networks implicated in myelination, which were lower in PSP temporal cortex (TCX) compared with AD. Some of these associations were retained even after adjustments for brain cell population changes. These TCX myelination network structures were preserved in cerebellum but they were not differentially expressed in cerebellum between AD and PSP. Myelination networks were downregulated in both AD and PSP, when compared with control TCX samples. Discussion: Downregulation of myelination networks may underlie both PSP and AD pathophysiology, but may be more pronounced in PSP. These data also highlight conservation of transcriptional networks across brain regions and the influence of cell type changes on these networks. Highlights: Brain myelination transcriptional networks are down in PSP and AD. Myelination networks are higher in AD vs. PSP but lower compared with controls. Network structures are preserved between temporal cortex and cerebellum.